Pengaruh Inisisasi Menyusui Dini (IMD) Terhadap Involusi Uterus Pada Ibu Post Partum Di Klinik Flora Kecamatan Kualuh Hulu Kabupaten Labuhanbatu Utara Tahun 2023 - Kolentina Hutajulu; Yasrida Nadeak; Marlina Simbolon; Friza Situmorang (Lembaga Pengembangan Kinerja Dosen, 2024)
One of changes that occur in puerperal ( post- partum is involution . uterus Involution or uterine contraction is a process uterus back into shape before pregnant . Uterine involution can also be regarded as the return of the uterus to its original state or condition before becoming pregnant. There are several factors that affect uterine involution including postpartum gymnastics. early mobility for maternal mothers, Early breastfeeding initiation, nutrition status, psychological age and parity factors. Early initiation of breastfeeding ( Inisiasi Menyusui dini or IMD ) is a breastfeeding process immediately after birth for 1 h. The purpose of research is to study influence of implementation early breastfeeding initiation ( IMD ) on the maternal uterine involution in BPS flora. This type of research is the study cohort analytic design Prospektive. Population and sample in this research is maternal in BPS flora in 2013 with techniques samples is concecutive sampling . The variables studied in this research is dependent and independent variables ,dependent variable studied were uterine involution while independent variables were early breastfeeding initiation (IMD). Quantitative data analysis include univariable and bivariate analysis with using t test. The results showed that average Height of uteri Fundus on day 6 postpartum that give Early Breastfeeding initiation ( IMD ) is 10,54 cm with standard deviation of 1.103 cm while Height of Fundus uteri in mother don;t give IMD is 13.33 with standard deviation 1,129 . based on statistical tests found an average difference both of them is p value of 0.000 with 95 % CI 2.143 to 3.440. There is a significant fundus height difference between mother that give IMD and who does not in BPS Flora . Health workers, particularly midwife are expected to be able to perform delivery assistance with IMD.